Re-purposing bridging flocculation for on-site, rapid, qualitative DNA detection in resource-poor settings. Issue 27 (26th January 2015) - Wee, E. J. H.; Lau, H. Y.; Botella, J. R.; Trau, M.
Abstract : A novel DNA mediated bridging flocculation assay was developed for evaluating amplified DNA in low resource settings. Abstract : Developing molecular diagnostics in resource-poor settings is challenging. As such, we purpose-built a novel bridging flocculation assay for qualitative evaluation of isothermally amplified DNA by naked eye. The flocculation assay was dependent on pH, DNA polymer amounts and lengths. The method was first applied to the rapid and sensitive detection of important plant pathogens and subsequently extended to other pathogens across the animal kingdom to demonstrate the wide applications of our approach.